Multiobjective Precoder Design for Coexisting Wireless Energy Transfer and Information Transmission Systems - Zhang, Haiyang; Huang, Yongming; Wang, Jiaheng; Wang, Baoyun; Yang, Luxi (IEEE systems journal, 2020)
This paper studies the precoder design for coexisting wireless energy transfer (WET) and wireless information transmission (WIT) systems, where WET and WIT share the same spectrum band, and the cochannel interference generated by one system is regarded as useful rather than harmful resource for the other system. Specifically, we address the transmit covariance design from the multiple-objective optimization perspective in order to simultaneously maximize the total harvested energy of energy receivers in WET and the secrecy rate of information receiver in WIT. To deal with the challenging multiple-objective optimization problem (MOOP), we first find the Utopia point of the MOOP. Then, we transform the original MOOP into two different single-objective optimization problems (SOOPs) via the weighted sum and the weighted Tchebycheff approaches, respectively. The two SOOPs are, however, nonconvex and nonsmooth. We further develop two iterative algorithms to tackle them, respectively. For comparison, a distributed transmit covariance design based on the Nash equilibrium is also proposed. Simulation results are finally presented to demonstrate the effectiveness of the proposed designs and illustrate the tradeoff between the total harvested energy and the secrecy rate.